Leadership in Educational Benchmarking: A Case Study on Principal Leadership at Madrasah Tsanawiyah in Pekanbaru - Herlina Permata Sari; Yayah Rahyasih; Asep Suryana; Diding Nurdin (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the role of principal leadership in implementing benchmarking at MTs Fadhilah Pekanbaru, focusing on public relations. Unlike conventional benchmarking studies that compare multiple aspects between schools, this research adopts a targeted approach, emphasizing the impact of public relations on school performance and reputation. A qualitative descriptive research design was used, centering on the principal and deputy principal responsible for public relations. Data were collected through interviews and analyzed using data collection, reduction, display, and conclusion techniques. The findings were then compared with relevant theories and prior research on benchmarking in education. The study found that implementing benchmarking in collaboration with MAN 1 Pekanbaru significantly improved public relations performance at MTs Fadhilah Pekanbaru. One of the key improvements was in external communication, evidenced by a structured and effective communication strategy. This included the strategic use of social media and digital platforms to enhance outreach and engagement with stakeholders. The findings highlight the effectiveness of focused benchmarking in improving public relations. The structured approach enabled the adoption of best practices, leading to enhanced school visibility and reputation. These results suggest that targeted benchmarking can serve as a model for improving other aspects of school management. This study demonstrates that benchmarking in public relations can be a valuable strategy for school improvement. Principal leadership plays a critical role in facilitating this process, ensuring that best practices are identified and integrated effectively. This approach has the potential to be expanded to other areas to enhance overall school performance.